Hello,
f(x) has as inverse f^(-1)(x)
and (fof^(-1))(x)=(f^(-1)of)(x)= x (the neutral function)
so h(f(x))=x
Answer:
-9 and 3
Step-by-step explanation:
as -9×3= -27
and
-9+3= -6
Answer:
Please where are the boxes
Answer:
hhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhh
Step-by-step explanation:hhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhjjjjjjjjjjjjjjjjjjjjjjhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhh